NOTES ON THE DISTRIBUTION OF EQUIVALENTS FOR VERBS FACERE, CREARE, AND GERMINARE - Stankovska, Petra (Bohemica Olomucensia, 2020)
The Book of Genesis at the place of latin creare has in younger translation of Croatian Glagolitic Vatican 5 breviary paleoslavonicism s'zdati very likely because it was known to the translator from Psalter. Otherwise we would expect the verb stvoriti as in older version of breviary. For germinare uses Vatican breviary expected common word vzrasti, while the older version, taken from Paroimiarion, has Old Church Slavonic prozebsti.
Keywords: Croatian-Glagolitic breviary; Bible; translation; Old Church Slavonic; Genesis